Discovering EFL Learners’ Reading Strategis at STKIP Muhammadiyah Aceh Barat Daya - Rini Susiani; Puan Tursina; Elia Mustika (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2019)
This study aimed to point out (1) whatkinds of reading strategies used by EFL students at STKIP Muhammadiyah Aceh Barat Daya? and (2) what is the common reading strategies used by those students?A quantitative research design was utilized to collect the data in which a questionnaire was used as instrument. The questionnaire consisted of items to gain the students’ responses toward six categories of Reading Strategies implementation on their reading ability, namely: memory, cognitive, compensation, metacognitive, affective, and social reading strategies. In total 50 students ofEnglish Education Department at STKIP Muhammadiyahfrom different semester were involved as participants.The findings of the study revealed that(1)EFL students at English Education Department used the six categories of reading strategies both direct and indirect reading strategies such as cognitive, compensation, affective, social, metacognitive and memory strategies. (2) The average range of the sixreading strategies obtained from EFL students at English Education Departmentwere above 3.5 to 4.4. This indicated that the common strategies used by EFL students at STKIP Muhammadiyah Aceh Barat were cognitive, compensation, affective, social, metacognitive, and memorystrategies.Keywords: Reading and Reading Strategy